2D Bi2WO6/MoS2 as a new photo-activated carrier for boosting electrocatalytic methanol oxidation with visible light illumination - Zhang, Hongmin; He, Jie; Zhai, Chunyang; Zhu, Mingshan (Chinese chemical letters, 2019)
A kind of new 2D heterojunction of Bi2WO6/MoS2 was constructed and used as visible-light activated carrier for depositing Pt electrocatalyst. With assistance of visible light irradiation, Pt-Bi2WO6/MoS2 composite shows enhanced electrocatalytic activity and stability towards methanol oxidation than traditional electrocatalytic process and commercial Pt/C. [Display omitted] In this paper, a new two-dimensional (2D)/2D composite of Bi2WO6/MoS2 was facile synthesized, and then was used as supporting material for depositing Pt nanoparticles. The as-synthesized Pt-Bi2WO6/MoS2 was extended into photo-assisted electrocatalytic oxidation of methanol, which is a model anode reaction for direct methanol fuel cell. Compare with traditional electrocatalytic process, Pt-Bi2WO6/MoS2 displays 1.5 times enhanced electrocatalytic performance on methanol oxidation with assistance of visible light irradiation and 2.2 times for commercial Pt/C. Besides, from the results of chronoamperometric and chronopotentiometry experiments, the stability of Pt-Bi2WO6/MoS2 electrode is clearly improved under visible light irradiation. The synergistic effects of photo- and electro-catalytic in the heterojunction of Pt-Bi2WO6/MoS2 in favor of the above enhancement. This research gives more insights in the fields of photo-assisted traditional electrocatalytic application by constructing of semiconductor heterojunction carrier.